2010
DOI: 10.1007/s00431-010-1214-7
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pneumococcal disease after implementation of a reduced three-dose pneumococcal conjugate vaccine program: a pediatric tertiary care center experience

Abstract: Following the implementation of a government-sponsored reduced three-dose (2 + 1) heptavalent conjugate pneumococcal vaccine (PCV7) program, we report a 61.4% decrease in the number of cases of invasive pneumococcal diseases (IPD) treated at our institution. Four years after the implementation of the three-dose reduced vaccine program, only 7.4% of IPD were caused by PCV7 serotypes, and there was an increase in the proportion of IPD caused by nonPCV7 serotypes; serotype 19A represented 40.7% of the strains iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Patrzałek et al investigated the influence of pneumococcal vaccination on the radiologically confirmed pneumonia admission rates in the hospital [8]. The results compare well with the 3+1 PCV7 dosing schedule [35][36][37].…”
Section: Effectiveness Of the Reduced-dose Schedule (2+1) In Childrensupporting
confidence: 53%
See 1 more Smart Citation
“…Patrzałek et al investigated the influence of pneumococcal vaccination on the radiologically confirmed pneumonia admission rates in the hospital [8]. The results compare well with the 3+1 PCV7 dosing schedule [35][36][37].…”
Section: Effectiveness Of the Reduced-dose Schedule (2+1) In Childrensupporting
confidence: 53%
“…Statistically significant declines were seen in all-cause pneumonia, pneumococcal pneumonia, and otitis media between the cohorts. The observed significant reduction in pneumococcal disease was non-inferior to that observed with the 3+1 dosing schedule [35][36][37].…”
Section: Effectiveness Of the Reduced-dose Schedule (2+1) In Childrenmentioning
confidence: 55%
“…For the 3 + 1 group, blood was sampled at 11 months (pre-booster) and 12 months (post-booster) Blood was sampled for immunogenicity testing at age 12 months for the 2 + 0 and 2 + 1 groups; the data from the 2 + 0 group were used for the pre-booster data, and the data from the 2 + 1 group were used for the post-booster data. For the 3 + 1 group, blood was sampled at 11 months (pre-booster) and 12 months (post-booster) Province of Quebec, Canada Trends in incidence rates of IPD [44] Crisinel et al Proportion of isolates that were vaccine serotype [45] Lernout and Sabbe (2008) Belgium National surveillance program 2, 4, 12 months…”
Section: Israelmentioning
confidence: 99%
“…The effectiveness of abbreviated dosing schedules of PCV-7 against IPD was evaluated in the USA [43], Canada [20,21,[44][45][46] and Europe [17][18][19][47][48][49][50][51]107]. These studies demonstrated that 2 + 1 schedules could be effective in the target age groups, notably in countries with good primary series uptake, compliance with the booster dose, and application of a catch-up program among older infants or children (see Table 1 for details of the vaccination programs).…”
Section: Effectiveness Against Ipdmentioning
confidence: 99%
“…The study published in this issue of the European Journal of Pediatrics reports on the surveillance of pediatric invasive pneumococcal infections in a tertiary care pediatric center in Quebec (Canada) after government sponsored introduction of PCV-7 vaccine for children up to age 5 years in a 2+1 schedule for infants [5]. Other reports mainly concern 3+1 schedules.…”
mentioning
confidence: 99%